2020
DOI: 10.1088/1742-6596/1622/1/012119
|View full text |Cite
|
Sign up to set email alerts
|

Control of a New Cycling Rehabilitation Robot Based on Fuzzy PID

Abstract: For completing the standardized rehabilitation training of the affected limb based on the lower limb rehabilitation training robot system, it is designed that a lower limb rehabilitation robot control system based on fuzzy PID control method to realize stable and accurate control of the rehabilitation training process. First of all, this paper analyzes the ranges of motion of human hip and knees, and a single degree of freedom lower limb rehabilitation training robot system based on the belt transmission princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is almost impossible to formulate an accurate mathematical model for nonlinear, time-varying, human-robot interacting systems [12][13][14]. In order to achieve better performance of controller, a lot of advanced control strategies have been employed to the passive control of lower limb rehabilitation robots including fuzzy control [15], sliding mode control [16], adaptive controller [17], neural network control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is almost impossible to formulate an accurate mathematical model for nonlinear, time-varying, human-robot interacting systems [12][13][14]. In order to achieve better performance of controller, a lot of advanced control strategies have been employed to the passive control of lower limb rehabilitation robots including fuzzy control [15], sliding mode control [16], adaptive controller [17], neural network control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Setting up the dynamic equation for each link is an essential factor to calculate and simulate the motion of the joints, from which it is possible to calculate the design of the mechanical structure and the controller so that it is suitable for research models. To establish the dynamic equation of the device [13][14], we conduct a dynamic analysis of the joints. The diagram of the dynamic analysis of the research model is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%